Parameter optimization: effect of humidity and fabrication process on flexural - Moor Syazalee Meor Sha; Rozli Zulkifli (Penerbit Universiti Kebangsaan Malaysia, 2022)
Biocomposite from kenaf reinforced polylactic acid (Kenaf/PLA) has the potential to replace a synthetic reinforcement and matrix in polymer composite applications. Kenaf is well known as a natural fiber that can be replaced with synthetic fiber and reinforced with synthetic resin, whether thermoset or thermoplastic. An increase in environmental impact drives increased usage of a biodegradable polymer such as PLA in the application of biocomposite. However, moisture uptake from the humidity and elevated temperature exposure during fabrication of composite is mostly a factor that affects the properties of biocomposite. Therefore, this study aims to optimize the factors consisting of humidity exposure, temperature and time holding during hot press using the design of experiment (DOE) by Box-Behnken Design (BBD) approach. The kenaf/PLA was exposed to the humidity range from 40% up to 80% before undergoing composite fabrication. Then produce the composite using a hot press molding where the parameter consists of elevated temperature (range from 160 o C up to 200 o C) and time holding (range from 3 minutes up to 10 minutes) that possibly affects the mechanical properties of kenaf/PLA. These three factors were evaluated based on optimizing maximum results on flexural properties, where all the combination factors were assessed using DOE. Using analysis of variance (ANOVA) revealed that humidity exposure and hot press temperature are essential factors affecting kenaf/PLA flexural strength. The results indicated that the selected humidity and hot press parameters were 40 %RH, 160 o C press molding temperature, and a 3-minute heating duration for optimal flexural strength. The parameter will obtain 111.61 MPa of flexural strength. Implementing the chosen factor can produce the kenaf/PLA biocomposite with an optimum flexural strength of 111.61 MPa.